Steroids interfere with human carbonic anhydrase activity by using alternative binding mechanisms - Alessio Nocentini; Alessandro Bonardi; Paola Gratteri; Bruno Cerra; Antimo Gioiello; Claudiu T. Supuran (Journal of Enzyme Inhibition and Medicinal Chemistry, 2018)
Bile acids have been shown to inhibit human (h) carbonic anhydrases (CA, EC 4.2.1.1) along the gastrointestinal tract, including hCA II. The elucidation of the hormonal inhibition mechanism of the bile acid cholate to hCA II was provided in 2014 by X-ray crystallography. Herein, we extend the inhibition study to a wealth of steroids against four relevant hCA isoforms. Steroids displaying pendants and functional groups of the carboxylate, phenolic or sulfonate types appended at the tetracyclic ring were shown to inhibit the cytosolic CA II and the tumor-associated, transmembrane CA IX in a medium micromolar range (38.9–89.9 µM). Docking studies displayed the different chemotypes CA inhibition mechanisms. Molecular dynamics (MD) gave insights on the stability over time of hyocholic acid binding to CA II.